Динамика одноконцевого канатного подъёмника с учетом направляющего шкива - Нестеров, А. П.; Осипова, Т. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
An analytical method determine the moments of forces of resiliency in resilient svyazyakh to the three-mass mechanical system taking into account mass of sending pulley